PENGGUNAAN MEDIA MANIPULATIF TERHADAP HASIL PEMBELAJARAN MATEMATIKA DI SEKOLAH DASAR - Mustika Hadi Permatasari; Bistari Bistari; Hery Kresnady (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThis study aims to analyze "The Effect of Manipulative Media Use on Student LearningOutcomes in determining the relationship between units of time, between units of lengthand between units of weight" The research method used is an experimental method withthe form of research Quasi Experimental Design, with experimental design Nonequivalent Control Group Design. The population in this study were all fourth gradestudents of SD Negeri 12 Pontianak city for the 2017/2018 school year. The sample inthis study consisted of 29 people from class IV A (manipulative media class) and 27people from class IV B (visual media class).The data collection tool is in the form of astudent learning outcome test, which is in the form of description questions with a totalof 10 questions. The average learning outcomes of the final class test usingmanipulative media were 83.48 and the average learning outcomes of the final classtest using visual media 72.66. Obtained the final test data t count of 3.1181 and t table(α = 5% and dk 29 + 27 -2 = 54) of 1.6671, because tcount (3.1181)> t table (1.6671),then Ha accepted. So, it can be concluded that there is an effect of the use ofmanipulative media on the learning outcomes of fourth grade students in mathematicslearning at 12 Pontianak City Elementary Schools. From the calculation of the effectsize (ES), the ES obtained is 0.80 (high criteria) .Keywords :Manipulative Media, Learning Outcomes, Mathematics